2022
DOI: 10.1111/1759-7714.14628
|View full text |Cite
|
Sign up to set email alerts
|

Promotor methylation status of MAPK4 is a novel epigenetic biomarker for prognosis of recurrence in patients with thymic epithelial tumors

Abstract: Background The prognosis of thymic epithelial tumors (TETs) currently relies on the commonly adopted WHO classification and Masaoka staging system, which cannot reflect the undefined biological behaviors limiting them as prognostic factors. Methods In this study, we first identified 40 genes and 179 genes, respectively that were epigenetically upregulated and silenced, corresponding to a total of 509 functionally methylated CpG sites between thymomas and thymic carcinom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…For validation purposes, they used univariate Cox regression to find methylation sites closely related to recurrence-free survival (RFS) in thymic epithelial tumors (TETs). However, multivariable Cox regression, incorporating forwarding selection for covariates, revealed that only a few characteristic features remained independent prognostic factors for RFS in TETs [140] . Using a similar Cox regression model approach, Wu et al, 2021 identified 166 independent prognosis-related CpG sites which were subjected to the consensus clustering method for finding a cluster showing the highest methylation sites associated with the risk scores.…”
Section: Dna Methylation Microarray Data Analysismentioning
confidence: 95%
See 1 more Smart Citation
“…For validation purposes, they used univariate Cox regression to find methylation sites closely related to recurrence-free survival (RFS) in thymic epithelial tumors (TETs). However, multivariable Cox regression, incorporating forwarding selection for covariates, revealed that only a few characteristic features remained independent prognostic factors for RFS in TETs [140] . Using a similar Cox regression model approach, Wu et al, 2021 identified 166 independent prognosis-related CpG sites which were subjected to the consensus clustering method for finding a cluster showing the highest methylation sites associated with the risk scores.…”
Section: Dna Methylation Microarray Data Analysismentioning
confidence: 95%
“… Cons: Assuming that continuous variables linearly influence the log hazard. [140] 18. 86 NDBS samples from two groups: (i) 45 DS-CHD (27 females, 18 males).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, in a recent investigation conducted by Guan et al, 40 genes and 179 genes were identified as epigenetically upregulated and silenced, respectively. This corresponds to a total of 509 functionally methylated CpG sites differentiating thymomas from TCs, as revealed by the analysis of the TCGA dataset [49]. The methylation β-values of cg20068620 in MAPK4 and cg18770944 in USP51 exhibited a significant correlation with Recurrence-Free Survival (RFS).…”
Section: Methylation Analysismentioning
confidence: 99%
“…The cellular pathways acknowledged the affect of methylation in TETs, including focal adhesion, regulation of actin cytoskeleton, natural killer cell-mediated cytotoxicity, calcium signaling, and other cancer-related pathways [103]. Two recent studies used DNA methylation data available in the Cancer Genome Atlas (TCGA) database to compare DNA methylation differences between TMs and TCs, revealing several epigenetic differences that will be detailed in the following section of this article [102,111]. Several previous studies based on the candidate gene approach have shown that tumor suppressor genes, such as human mutL homolog 1 (hMLH1), O-6-methylguanine-DNA methyltransferase (MGMT), cyclin-dependent kinase inhibitor 2A (CDKN2A), ras association domain family member 1 (RASSF1A), and many other genes are less frequently methylated in early-stages TMs, as compared to invasive TMs and TCs [94,95,98,99,101].…”
Section: Thymomasmentioning
confidence: 99%
“…A more recent analysis of the TCGA dataset identified 40 upregulated and 179 silenced genes, as well as more than 500 DMC, between TMs and TCs. Among them, methylation of cg20068620 in mitogen-activated protein kinase 4 (MAPK4) was significantly associated with recurrence-free survival (RFS) in both the 124 TETs included in the TCGA dataset and in a replication cohort of 95 TET patients [111].…”
Section: Thymic Carcinomasmentioning
confidence: 99%